Measurement of electrophysical parameters of alcoholic solutions - Pokhodylo, E.; Yuzva, V. (Видавництво Львівської політехніки, 2015)
Mathematical models are analyzed which describe active and reactive components multielement two-terminal admittance, which provides system "electrode-alcohol solution."
Keywords: admittance; capacity double layer; dielectric conductivity; specific conductance